The Analysis of Independent Learning Activities Unit-Based Learning on Senior High School Students - Astriani, Erni; Widjaja, Sri Umi Mintarti (Unversitas Negeri Malang, 2019)
This study aimed at assessing the implementation of Independent Learning Activities Unit-based learning. This study used a descriptive qualitative method with a phenomenological approach. Selection of research subjects using purposive sampling method. Data collection uses two techniques, including: in-depth interviews and observation. The results of this study include: (1) The teacher has carried out several activities that can encourage student activeness but some activities in learning have not been carried out in accordance with the principles of Independent Learning Activities Unit, these activities include: in encouraging student participation, the teacher has not emphasized participation in thinking, test formative is done by students in groups which should be done independently and the teacher does not use the results of the formative test to determine whether these students can continue to the next Independent Learning Activities Unit or not. (2) students in the fast learner category have used Independent Learning Activities Unit according to the principle of student active and complete learning, while for students who are medium and slow learners have not fully used Independent Learning Activities Unit according to the principles of student active and complete learning.Â Â